Architectural Development of Mosques in Pattani Province - Tapparut, Tanasun (NAJUA: History of Architecture and Thai Architecture, 2022)
This research article explores the architectural changes of mosques in Pattani Province that occurred in the midst of changing social, economic and political conditions. The scope of the study is from the spread of Islam in Pattani Province in the 19th century to the present days. The research asks what factors contributed to the change and existence of mosque architecture in Pattani. This qualitative research was conducted using a total of 7 mosques: Aho Mosque, Najmuddin Mosque, Krue Se Mosque, Dato Mosque, Rayafatani Mosque, Raya Mosque, and Central Mosque of Pattani Province. The criteria for the selection are from case studies related to the history of Pattani and the ones that appear to have significant changes in architectural style, distinctive from the previous mosques in Pattani. Drawing upon field surveys, maps, photographs and in-depth interviews, the study then analyses the changes in architectural styles. The finding reveals that the factors that caused the change in the architecture of mosques in Pattani Province came from two principal causes. First, the internal factor: the adoption of local architectural styles as an inspiration for the formation of present mosque architecture. Second, external influences: the appropriation of architectural styles from Persian culture to the architecture of mosques in Pattani. By adopting the Mughal architectural style and onion-shaped domes, the Central Mosque of Pattani served as a popular model for other mosques in Pattani Province and neighbouring provinces. While the architectural style of mosques in Pattani has changed over time, such changes occurred merely externally. The layout of the mosques remains oriented along the East-West longitudinal direction. The front of the mosque always faces Eastward, to facilitate users who enter the building to turn westward to Qibla's direction when praying. Nowadays, the mosque continues to serve as the centre of the community. Especially on Friday as well as other religious days, people in the community will gather at the mosque. This reflects the importance of the mosque and the strict adherence to the teachings of Islam of the people in Pattani.